PERANAN PUSAT PELAYANAN TERPADU PEMBERDAYAAN PEREMPUAN DAN ANAK DALAM PEMULIHAN KORBAN PELECEHAN SEKSUAL ANAK DI KABUPATEN PELALAWAN (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Human rights are fundamental rights that are inherently inherent in human beings,are universal, and bestowed by God Almighty. In the protection of human rights, children arealso included. Child is someone who is not yet 18 (eighteen) including a child who is still in thewomb. Child protection efforts must begin as early as possible, but in reality it is still oftenheard that children are victims of sexual abuse and there are still many children whose rightshave not been fulfilled to date. The purpose of this paper is: first, to determine the extent of therole of integrated service centers for women and children empowerment in the recovery ofvictims of child sexual abuse in Pelalawan District, secondly, to find out what constraints facedby integrated service centers empower women and children in recovery of victims of childsexual abuse in Pelalawan District, thirdly, to find out what efforts should be made so that theintegrated service center for women's and children's empowerment can be maximized inrestoring victims of child sexual abuse in Pelalawan District.This type of research can be classified in the type of sociological juridical research,because in this study the author immediately conducts research on the location or place understudy in order to give a complete and clear picture of the problem under study. This researchwas conducted in Pelalawan District P2TP2A, while the population and samples were allparties related to the problems examined in this study, data sources used, primary data,secondary data and tertiary data, data collection techniques in this study with interviews andstudies literature.From the results of the problem research there are three points that can beconcluded. First, the Recovery of Victims of Child Sexual Harassment in Pelalawan District hasnot yet proceeded as it should, secondly, Constraints when dealing with parents of victims,Making agreements with the police, Conducting dialogues and mediation, Constraints thatcome from reporters and while Lack of Public Awareness, third, Effort must P2TP2A Unit doesa good collaboration between P2TP2A personnel and P2TP2A Unit so that they help andunderstand each other in carrying out their duties to provide protection for child victims. Theauthors, first, prevent and eradicate child sexual abuse, secondly, provide important guidanceto parents children, thirdly, the P2TP2A Unit and the Pelalawan District police ranks mustfurther enhance cooperation between communities.Keywords : Role-P2TP2A-Recovery of Child-Sexual Abuse-Victims